2007
DOI: 10.1103/physrevb.75.020511
|View full text |Cite
|
Sign up to set email alerts
|

Anisotropic gap of superconductingCaC6: A first-principles density functional calculation

Abstract: We report first-principles calculations of the superconducting properties of CaC 6 , obtained within the density functional theory of superconductivity. We find a moderately anisotropic gap which is larger on the Fermi surface sheet with interlayer and Ca character compared with isotropic calculations. Our calculated anisotropy improves the agreement with specific heat experiments and is consistent with recent tunneling experiments. In contrast to MgB 2 , we do not find multigap superconductivity but, instead,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

28
133
3

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 117 publications
(164 citation statements)
references
References 21 publications
28
133
3
Order By: Relevance
“…There are several reported FS, determined both experimentally 17,35 and theoretically 36,37 . These all exhibit the potential for nesting, namely that they have high symmetry, extended parallel portions of FS and significant density of states around the Fermi level.…”
Section: Discussionmentioning
confidence: 99%
“…There are several reported FS, determined both experimentally 17,35 and theoretically 36,37 . These all exhibit the potential for nesting, namely that they have high symmetry, extended parallel portions of FS and significant density of states around the Fermi level.…”
Section: Discussionmentioning
confidence: 99%
“…It is then possible to restrict the Matsubara integration to a low energy ( a fraction of eV ) by a renormalization procedure ” → ” * introduced by Morel and Anderson 5,27,31 . ” * can be calculated within the random phase approximation 22,28,29 (RPA) and the resulting T c are usually in reasonable agreement with experiments 23,30 . However, usually ” * is adjusted to obtain the experimental T c .…”
Section: Methodsmentioning
confidence: 97%
“…First-principles theoretical investigations on CaC 6 revealed that the superconducting critical temperature can be explained considering only the electron-phonon mechanism 47,48 , even if other pairing mechanisms were proposed (excitonic and plasmonic).…”
Section: B Cac6mentioning
confidence: 99%